(untitled) (Global Journal of Science Frontier Research, 2024)
Impulse loading of a sample of limited dimensions (at least two free surfaces) leads to the oscillation of the sample in the standing wave mode as a consequence of wave reflection from the faces and their interaction with each other. Localized strain bands originate and evolve at the standing wave nodes (wave interference zone), where the deformation of the material occurs in the compression-tension mode and the stress in the wave interference zone does not exceed the spall strength of the material. (Excessive stress leads to the formation of spall cracks and sample destruction). As a result of the absence of energy transfer through the nodal points, which is typical of standing waves, the deformation of the sample can last for a long time after passing a shock wave until dissipative processes would bring about oscillatory process damping. Another characteristic feature of standing waves is the formation of new harmonics with their own wavelengths and vibration eigen frequencies with new spall damage occurring at each node.